2015
DOI: 10.1016/j.expneurol.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibitory effect of riluzole on trophic factor production

Abstract: Riluzole is the only FDA approved drug for the treatment of amyotrophic lateral sclerosis (ALS). However, the drug affords moderate protection to ALS patients, extending life for a few months by a mechanism that remains controversial. In the presence of riluzole, astrocytes increase the production of factors protective to motor neurons. The stimulation of trophic factor production by motor neuron associated cells may contribute to riluzole’s protective effect in ALS. Here, we investigated the effects of media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(63 reference statements)
0
9
0
1
Order By: Relevance
“…Interestingly, riluzole may also confer protection by increasing the trophic support provided by astrocytes [207]. However, chronic riluzole treatment has an inhibitory effect on trophic factor production by astrocytes, suggesting that adjustments in the administration regimen could be beneficial [208]. Different growth factors such as glial cell line-derived neurotrophic factor (GDNF), insulin-like growth factor I (IGF-I), ciliary neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) have been evaluated in experimental models of ALS [209212].…”
Section: Therapeutic Potential Of Astrocytesmentioning
confidence: 99%
“…Interestingly, riluzole may also confer protection by increasing the trophic support provided by astrocytes [207]. However, chronic riluzole treatment has an inhibitory effect on trophic factor production by astrocytes, suggesting that adjustments in the administration regimen could be beneficial [208]. Different growth factors such as glial cell line-derived neurotrophic factor (GDNF), insulin-like growth factor I (IGF-I), ciliary neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) have been evaluated in experimental models of ALS [209212].…”
Section: Therapeutic Potential Of Astrocytesmentioning
confidence: 99%
“…Some of the events characterizing ALS are: the aggregation and misfolding of proteins, high levels of oxidative stress, excitotoxicity, deficient axonal transport, mitochondrial dysfunctions and inflammation 3 . The neurodegeneration occurring in ALS has also been described as a non-cell autonomous occurrence 4 , meaning that the MN death is a consequence of a pathological state of other cell types, such as microglia 5,67,8 , astrocytes 915 and oligodendrocytes 16,17 that either spread their toxicity or simply provide less support compared to a non-pathological condition.…”
Section: Reviewmentioning
confidence: 99%
“…One possibility is that it may act synergistically on three independent pathways: the inhibition of the glutamic acid release, a non-competitive blockage of the Nmethyl- D-aspartate receptor mediated-responses, and a direct action on the voltage-dependent sodium channels 64 . Additionally, some investigations have shown Riluzole also stimulates the release of trophic factors from gliomas, astrocytes, and Schwann cells 6567 . The efficacy of this treatment was demonstrated in two double-blind, placebo-controlled clinical trials 68,69 .…”
Section: Reviewmentioning
confidence: 99%
“…Other authors have shown the promoting effect of riluzole on dendrite outgrowth (Bergerot et al, 2004) and also stimulation of neurotrophic factor (GDNF and BDNF) production in astrocytes (Mizuta et al, 2001). While acute riluzole incubation induced CT-1 secretion by astrocytes and Schwann cells, chronic treatment induce a significant decrease in trophic factor production compared to untreated cultures (Dennys et al, 2015). !…”
Section: Experimental Strategies To Prevent Motoneuron Loss After Venmentioning
confidence: 96%